2013
DOI: 10.1007/s00415-013-7068-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in fatal disease: the flawed judgement of the social environment

Abstract: Decisions to prolong or shorten life in fatal diseases like amyotrophic lateral sclerosis are strongly influenced by healthy individuals, such as caregivers and physicians. Furthermore, many believe that amyotrophic lateral sclerosis (ALS) patients should decide ahead of time on advanced directives to circumvent confounding effects of subsequent cognitive impairments. The ability of healthy persons (caregivers and age-matched healthy subjects) to anticipate patients' quality of life (QoL), depression and vital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 38 publications
5
63
0
Order By: Relevance
“…However, this might be explained by the fact that, in accordance with previous studies investigating the incidence of depression in ALS, 21 the share of patients with depression was surprisingly low, offering little room for improvement after NIV initiation. Therefore, a standardized quality of life score appears to be a more useful tool in this regard and should be considered in future studies.…”
Section: Discussionsupporting
confidence: 51%
“…However, this might be explained by the fact that, in accordance with previous studies investigating the incidence of depression in ALS, 21 the share of patients with depression was surprisingly low, offering little room for improvement after NIV initiation. Therefore, a standardized quality of life score appears to be a more useful tool in this regard and should be considered in future studies.…”
Section: Discussionsupporting
confidence: 51%
“…Considering that social interaction, among the cognitive aspects that may impact adherence to treatment and patients’ quality of life (QoL), has been increasingly shown to be impaired in neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS; Elamin et al, 2012; Santangelo et al, 2012; Yamada et al, 2015; Burke et al, 2016a), an early assessment of this domain in the disease course could be useful for positively conditioning patients’ management and prognosis. In particular, with regard to ALS, a multisystem neurodegenerative disease, not only characterized by motor dysfunctions, but also by extra-motor symptoms, belonging to the clinical and pathological spectrum of FTLD (Lillo et al, 2012; Ling et al, 2013; Trojsi et al, 2015; Burrell et al, 2016), the growing evidence of social cognition impairments may have important implications on patient’s QoL and ability to engage competently in end-of-life decisions (Chiò et al, 2004; Lulé et al, 2013; Körner et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown similar QoL for ALS patients and their next of kin (NOK) studies on patients prior to developing LIS have shown, with the latter significantly underestimating patients’ QoL …”
mentioning
confidence: 99%